Simulation Design of Traditional Costumes Based on Digital Printing Technology (Journal of Fiber Bioengineering and Informatics, 2016)
This paper deals with the research on simulation design of traditional Chinese costumes in digital method.We take Chi-pao (Cheongsam), the Mandarin gown of the Qing Dynasty as the research object andconduct a comprehensive analysis of its structures, colors, patterns and other traditional crafts. Thena simulation digital design is made and cutting pieces are printed through digital printer. The finishedproduct shows that the simulation of traditional costumes through this method is feasible to achievesatisfactory results. Thus, simulation design can be used as one of the ways to research, inherit andspread the traditional Chinese costumes.
Keywords: Simulation Design; Traditional Costumes; Garment CAD; Digital Printing; Embroidery